Quantification of inter-limb asymmetries in male professional volleyball players by rate of force development, maximal voluntary force and force steadiness - D'Emanuele, S.; Boccia, G.; Zardo, V.; Durigon, V.; Schena, F.; Tarperi, C. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Inter-limb asymmetries have been identified as a potential factor that may contribute to impaired sports performance and possibly increase injury risk, especially in sports that involve many asymmetrical actions, such as volleyball. We had a dual aim: to investigate if muscle function asymmetries are muscle-specific or if one side is overall more performative independently of the muscle group; and to investigate if, within each muscle group, asymmetry direction is consistent among various muscle performance and motor control metrics. METHODS: 13 professional male volleyball players (24±3 yrs; 87±7 kg; 194±7 cm; 12±4 yrs of practice; 19±2h training/week) took part in our study. The subjects were seated on a bench with the arm flexed at 90°. The wrist was aligned and fixed with custom-built telescopic support connected to a strain gauge load cell to record compression/extension forces. After familiarisation, participants performed two maximal voluntary contractions (MVC) and 40 submaximal and maximal ballistic contractions to assess the Rate of Force Development Scaling Factor (RFD-SF) and RFD at peak (RFDpeak), and in time-locked intervals (RFD50,100,150). Furthermore, participants performed two contractions lasting 8s to assess force steadiness as Approximate Entropy (ApEn), Coefficient of Variations (CoV), and Detrended Fluctuation Analysis (DFA*). These evaluations were repeated randomly for both limbs elbow extensors (EE) and flexors (EF). Repeated measure ANOVA assessed each metrics differences between muscle groups and limbs. Kappa coefficients (K) were calculated to determine the levels of agreement for the direction of asymmetry among muscle groups and performance metrics at the individual level. RESULTS: MVC of EF was greater in the dominant vs non-dominant side (MVC = 12%, p=.007, d=.68), while no differences were achieved for the other metrics. The asymmetry direction agreement between muscle performance metrics was null for all parameters except for CoV, which resulted in slight (K=0.153) and fair (K=0.234) for ApEn. The agreement between RFDpeak and MVC (K=0.211) was appropriate, slight between RFDpeak and RFD-SF (K=0.178), and null when comparing RFDpeak with CoV, ApEn and DFA*. CONCLUSION: Although volleyball is considered a sport with an asymmetrical nature, the overall muscle symmetries observed in this study did support this hypothesis. Our results demonstrate that asymmetries are muscle-specific and rarely favour the same side across different muscle performance metrics, regardless of dominance. Generally, at the individual level, no side proves more performant than the other, not even at the level of variability and complexity of the force output: each limb is favoured depending on the muscle group and performance metric. Strength and conditioning coaches who wish to address asymmetry levels can use the current findings, as they should prescribe specific training for each goal.